Just going to the dentist - Mayer, Mercer, 1943- (Racine, Wis. : Western Pub. Co., 1990)
Little Critter goes to the dentist for a checkup, and finds that going to the dentist isn$1 (Bt so bad.s
"A Golden book, New York."